EDUKASI MELALUI PEER GRUP BERPENGARUH TERHADAP PENGETAHUAN DAN SIKAP TENTANG PERSONAL HYGIENE - Sibarani, Eirene Rosalina; Riyadi, Agung; Lestari, Widia (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
According to Riskesdas data in 2015, found most of the diseases that attack school-aged children are caused due to lack of personal hygiene. This is because the lack of knowledge of children will be personal hygiene. The purpose of this study to determine the effect of educational methods through peer group on knowledge and attitudes about personal hygiene. This type of research is pre experimental with one group pretest-posttest design. Samples taken amounted to 30 people using side porposive technique. Data analysis was done by T-Paired test. The results showed that the average knowledge before the intervention was 10.93 and after the education became 17.30. Average attitude before intervention 55, 20 and after intervention to 72,67. There was a significant increase between the mean knowledge before and after the given peer group education (P = 0,000 in α ≤ 5%.). There is a significant difference in attitude before and after education through peer group (P = 0,000 in α ≤ 5%.) In children in SD N 37 Kota Bengkulu Year 2017. It is suggested to sekolh teachers to use the peer group education method as a method of learning personal hygiene at school.